Work-Sampling Study of an Innovative Care Coordination Program Aimed at Children With Chronic Health Conditions. Issue 6 (November 2020) - Talon, Brian; Gerges, Michael; Perry-Bell, Kenita; Caskey, Rachel N.; Van Voorhees, Benjamin; Martin, Molly A.; Touchette, Daniel R.
Abstract : Purpose of Study: To estimate time allocation and labor cost for care coordinators (CCs), community health workers (CHWs), and mental health workers (MHWs) to conduct care coordination tasks in a pediatric care coordination program. Primary Practice Setting: A public tertiary academic medical center in Chicago, IL. Methodology and Sample: A work-sampling study was conducted using a text message-based survey on 5 CCs, 20 CHWs, and 4 MHWs who volunteered to participate. Workers were randomly sampled within working hours to collect information on who was the subject of interaction and what service was being delivered over a 6-month period. Time allocation of workers to different subjects and services was summarized using descriptive statistics. Results: Care coordinators allocated 41% of their time to managing CHW teams. Community health workers allocated 37% of time providing services directly to children and 26% to the parent/caregiver. Mental health workers allocated 16% of time providing services to children and 29% to the parent/caregiver. The care coordination program serviced 5, 965 patients, with a total annual labor cost of $1, 455, 353. Implications for Case Management Practice: Community health workers spent the majority of time working with patients and their families to conduct assessments. Mental health workers primarily addressed children's needs through their caregivers. Care coordinators primarily supported CHWs in coordinating care. Results may be used to inform development of such programs by determining services most often utilized, and labor cost may be used to inform program implementation and reimbursement.